Developing Teaching Materials for Writing Explanatory Texts Based on Google Form File Upload Options Using Innovative Strategies - Fitria Wulandari; Cristina Br Sitorus; Elisabet Simanjuntak; Piladelpia Trifosa B Ginting; Trisnawati Hutagalung; Nurul Azizah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This development research aims to describe: 1) the procedure for developing teaching materials for writing explanatory texts based on Google Form file upload using innovative strategies for grade XI of high school; 2) the profile of teaching materials for writing explanatory texts based on Google Form file upload using innovative strategies for grade XI of high school as a result of the development. This research took place in the odd semester of the 2025/2026 academic year. This research used the R&D method through ADDIE modification. The research population for the trial of the revised product was 30 grade XI students of SMA Santo Thomas 2 Medan. This research used a total sample. Data on the learning process in the product trial were collected using observation guidelines. A questionnaire for the closed-type weighing team was used to validate the data and the results of qualitative data analysis. Another questionnaire was used to weigh the teaching materials per type of feasibility. Quantitative data used a checklist. Pre-test-posttest data for writing explanatory texts were collected using a performance test instrument based on Google Form file upload option. Research results: 1) development of teaching materials for writing explanatory texts based on Google Form file upload using innovative strategies for grade XI SMA contains the following procedures: a) basis analysis; b) design preparation; c) design development; d) initial product trial; e) evaluation and revision of initial products; f) trial of revised products; g) evaluation and revision of revised products; h) reproduction of final products; 2) structure of the final product of teaching materials for writing explanatory texts based on Google Form file upload using innovative strategies for grade XI SMA: a) section-1 contains student attribute forms; b) section-2 contains descriptions of materials and examples of explanatory texts combined with copying task techniques; c) section-3 contains tests as learning techniques; d) section-4 contains evaluation of writing explanatory texts using the take home examination system.